Impact of Postgraduate Qualifications on the Career Progression of Middle Leaders in Schools - Ben Archer (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2021)
With a highly competitive higher education market in Australia, there is a significant push for professionals to obtain further qualifications. While much has been written on the progression to Principalship in schools, there is a paucity of writing on the progression into Middle Leadership. A survey of middle leaders in Australian schools indicate that the skills learned in postgraduate qualifications are highly valued by people entering Middle Leadership, however, no impact is recorded in relation to progression into further leadership roles. This research has the potential to influence the career decision making of school teachers and leaders, as well as influence the marketing of postgraduate qualifications by higher education providers.